Performance evaluation methods for librarians in selected colleges and university libraries in Metro Manila a survey - Elverio, Hilaria A.; Tamesis, Angelina R.; Tann, Filomena M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1990)
This research study provides an overview of the academic libraries in Metro Manila which conduct performance evaluations of their librarians. Specifically, the survey reviews the reasons for and the manner of conducting performance appraisals, the different appraisal methods used, and the problems encountered with the different appraisal methods used including the potential pitfalls of performance evaluations. Thirty-three selected college and university libraries in Metro Manila served as the respondent intitutions for the study. The study used the descriptive survey method of research. The survey questionnaire was the instrument used in gathering the data.
The research findings showed that : (1) fifty-seven percent of the total respondents were found to be conducting regular performance appraisals of their librarians; (2) the three important reasons given for conducting performance evaluations were for performance reviews, reward reviews, and potential reviews; (3) among the wide variety of appraisals currently in use are the essay method, ranking method, simple ranking, alternative ranking, paired comparison, forced distribution, graphic rating scale, management by objectives, peer evaluation, behaviorally anchored rating scale, performance against job description, on-the-spot performance evaluation, and a combination of methods; (4) the graphic rating scale appeared to be the most popularly used single method in the academic libraries surveyed, followed by the simple ranking method and the comparison of actual performance against job description; (5) while all of the respondents use performance evaluation forms, the majority use institutional forms because of the unavailability of performance appraisal forms for librarians; and (6) all of the respondents were, in one way or the other, beset with problems in the performance evaluation methods they used.
Some of the conclusions drawn were that : (1) 57 percent of the academic libraries in Metro Manila periodically review the performance of their librarians; (2) in general, performance appraisals are regarded as useful tools which serve a variety of purposes in library management; (3) there is no best appraisal system, but a viable one will contain validated rating methods, have evaluations based on hard criteria, provide for consistency in the ratings of its appraisers, and be resistant to rater-error tendencies; (4) there is a feeling of dissatisfaction especially among those who use institutional forms because they feel that these forms do not clearly spell out the standards against which they are to be judged; and finally, (5) the positive response of the majority of the respondents is encouraging and a vital sign of their recognition and understanding of the benefits that performance evaluations can offer.
In the light of the foregoing, the following recommendations are proposed : (1) for all academic libraries that still do not have formal ratings, to select an appropriate rating method or a combination of methods which will systematically evaluate the work performance of their librarians; (2) for all the subjects of the study especially those who are using institutional forms for their evaluations, to develop their own evaluation forms specifically for their librarians; (3) for all academic libraries, to carry out the training of their raters in the conduct of performance appraisals seriously because the success of the rating process depends largely on the skill and attitude of raters; and (4) a model appraisal form (Appendix B) is submitted as the researcher's concept of a working performance evaluation form.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Librarians--Rating of; Libraries, University and college--Metro Manila; Library employees--Rating of